Fe3O4-nanoparticles catalyzed an efficient synthesis of nitriles from aldehydes. Issue 32 (10th August 2016) - Ghosh, Pranab; Saha, Bittu; Pariyar, Gyan Chandra; Tamang, Abiral; Subba, Raju
Graphical abstract: Highlights: Easy reaction set up. Simple and easy workup procedure. Economically benefited. Abstract: Fe3 O4 -CTAB NPs have been applied as a competent catalyst for one-pot synthesis of nitriles directly from aldehydes. The present investigation describes the synthesis of nitriles by combination of aromatic/aliphatic/heterocyclic aldehydes and hydroxylamine hydrochloride in the presence of iron oxide nanocatalyst in DMF under reflux condition. Fe3 O4 -CTAB NPs were prepared by reported method and characterized by FE-SEM, TEM, and XRD analysis. The amount of Fe in Fe3 O4 -CTAB was quantified by Atomic Absorption Spectroscopy (AAS). The protocol endow with excellent yield of products along with simple reaction set up and economically adept alternative approach.